The Interplay of Cognition and Genre-Based Instruction in English Writing Development - Asbar, Asbar; Mahmud, Murni; Halim, Abdul (Universitas Cokroaminoto Palopo, 2025)
The development of effective English writing skills is a persistent challenge for learners, particularly in English as a Foreign Language (EFL) contexts, where cognitive and linguistic demands often overwhelm students. This study examines the role of Genre-Based Instruction (GBI) in addressing challenges by exploring its interaction with cognitive processes on writing proficiency. Specifically, the research explores how GBI contributes to students’ understanding of genre structures, promotes cognitive engagement in planning and organizing writing, and cultivates critical thinking. Employing a qualitative approach, data were collected through interviews involving 20 secondary school students. The results highlighted how GBI facilitated students' understanding of genre-specific conventions, enabling them to create texts with greater cohesion and coherence. Students also reported that the structured steps inherent in GBI reduced cognitive load and enhanced their ability to plan and organize ideas systematically. Furthermore, the study highlighted GBI’s role in motivating students by providing clear guidance and relevant content, which increased their confidence and enthusiasm for writing tasks. These findings underscore the potential of GBI to address the multifaceted challenges of writing by integrating cognitive and pedagogical strategies, offering actionable insights for educators and curriculum designers.